A Study of the Incidence and Outcome of Fungal Infections in the Neonatal Intensive Care Units; A Seven-year Surveillance: Fungal Infections in NICU - Sharifi, Salma; Mosayebi, Ziba; Valizadeh, Mohammad; Moghtaderi, Mastaneh (Journal of Pediatric Nephrology, 2025)
Background and Aim: Candida infections are rare in the neonatal period, but they are an important cause of morbidity and mortality in neonatal intensive care units. Invasive fungal infections are extremely difficult to diagnose. It is suggested to start empirical treatment with antifungal therapy in high-risk, low-birth-weight infants who do not respond rapidly to antibacterial therapy or in those who are in a septic state due to an unknown source, based on regional guidelines. The aim of this study was to facilitate the earlier detection of at-risk newborns to initiate antifungal therapy as soon as possible, thereby lowering mortality rates and serious permanent disabilities. Methods: This is a retrospective cross-sectional observational study on newborns admitted to the neonatal intensive care unit (NICU) from March 2010 to February 2016. Risk factors, such as birth weight, sex, route of delivery, the timing of oral feeding, total parental nutrition (TPN), prescribed drugs (such as antibiotics, H2 blockers, methylxanthine, vasopressors, and corticosteroids), underlying diseases, history of surgery, urinary catheter insertion, central venous catheterization, and mechanical ventilation were extracted from patients’ files. Also, we analyzed the blood groups of patients to find any possible relation to fungal infections. Results: During the seven-year period, 2927 newborns were admitted to the NICU, of whom 32 patients (1.1%) were infected by fungal microorganisms. All but one of these neonates were infected by C. albicans. Most of them had positive urine or blood cultures for C. albicans (48.8% and 27.9%, respectively). All of our patients received amphotericin B as standard therapy, resulting in a 75% recovery rate. Conclusion: Surveillance of newborns with underlying risk factors aids in early decisionmaking to start treatment for fungal infections in high-risk groups, thereby decreasing mortality rates and long-term devastating complications.